Premonition - Yapo, Mennan; Amritraj, Ashok; Jashni, Jon; Shankman, Adam; Gibgot, Jennifer; Perkash, Sunil, ca. 1970-; Kelly, Bill; Bullock, Sandra; McMahon, Julian, 1968-2025; Tri-Star Pictures; Metro-Goldwyn-Mayer Film Co.; Hyde Park Entertainment (Firm); et al. (United States : Sony Pictures Entertainment, 2007)
A depressed housewife, who learns her husband was killed in a car accident the previous day, awakens the next morning to find him alive and well at home. The day after she awakens to a world in which he is still dead.
Copyright: Premonition Pictures, Inc. PREV: Screenplay prev. reg. 2005, PAu 2-993-474; prev. pub. musical compositions & sound recordings of compositions.; prev. pub. film & television clips. NM: all other cinematographic material. DCR 2007; PUB 15Mar07; REG 16Mar07; PA1-365-091.
Summary adapted from Internet movie database, viewed Jan. 23, 2008.
Digital sound on two compact discs stored in one film can (CGE 1529).
Not viewed.
Sources used: Copyright data sheet; Copyright database; Variety Web site, review posted Mar. 11, 2007, viewed Jan. 23, 2008; Internet movie database, viewed Jan. 23, 2008; FirstSearch, OCLC 123422992, viewed Jan. 23, 2008.
Executive producers, Andrew Sugerman, Nick Hamson, Lars Sylvest ; camera, Torsten Lippstock ; editing, Neil Travis ; music, Klaus Badelt.
Keywords: Housewives -- Drama; Marriage -- Drama; Husband and wife -- Drama; Traffic accidents -- Drama; Family -- Feature